Analisis Inovasi Pendidikan Kesetaraan Paket C Pada Homeschooling Primagama (Hspg) Bandung - Wulan Rahmayanti; Supriyadi (Universitas Dr. Soetomo Surabaya, 2024)
This study discusses the Innovation of Package C Equivalency Education implemented in Homeschooling Primagama Bandung, including knowing the problems and impacts implemented from the innovation. The research method used is a qualitative descriptive method, by conducting field observations, interviews and documentation. The results of the study obtained are the innovations applied to Homeschooling Primagama (HSPG) Bandung including teacher innovation, curriculum or learning innovation and supporting facility innovation. Teacher innovation is by using psychological and academic approach methods, while for the curriculum or learning, it uses the national and international curriculum, the national curriculum consists of the 2013 curriculum and the independent curriculum with a modular system. The international curriculum applied in Homeschooling (HSPG) bBandung is by implementing the Cambridge International Examination (CIE) curriculum. For supporting facility innovation, Homeschooling Primagama (HSPG) Bandung provides talent and interest development for all students, both those who take the community, independent or individual class system. The problems faced when implementing this innovation are from Human Resources which are still limited and there are several conflicting learning schedules. The impact of the innovation that has been implemented has a significant impact on improving student development and skills, increasing lea rning independence, improving communication skills and other developments